A Novel SACS Variant Identified in a Chinese Patient: Case Report and Review of the Literature - Chen, Yuchao; Lu, Xiaodong; Jin, Yi; Li, Dan; Ye, Xiaojun; Tao, Chenjuan; Zhou, Menglu; Jiang, Haibo; Yu, Hao (Frontiers in Neurology, 2022)
Mutations in the SACS in gene have been linked with autosomal recessive spastic ataxia of Charlevoix Saguenay (ARSACS). It is a clinically and genetically heterogeneous disease characterized by slow progressive ataxia, spasticity and sensorimotor neuropathy and a combination of other manifestations, such as lacking spasticity, hearing loss, and epileptic seizures, etc. Currently, there have been very few case reports regarding SACS gene mutation in Chinese patients. Here, we describe a 35-year-old Chinese patient carrying a novel variant in SACS (c.11486C>T) presented with progressive ataxia and demyelinating peripheral neuropathy. Then, we reviewed 22 Chinese cases carrying SACS gene mutations, including our patient. All of them had the symptom of cerebellar ataxia gait and showed cerebellar atrophy on brain MRI. A total of 28 SACS mutations were identified in those patients. Our study further expands the mutation spectrum of SACS gene, and contribute to the evaluation of genotype-phenotype correlations.